Uveitis : A Practical Guide to the Diagnosis and Treatment of Intraocular Inflammation - Papaliodis, George N. (Springer International Publishing : Imprint: Springer, 2017)
Written as a practical guide for the diagnosis and treatment of uveitis, this text provides uveitis specialists, practicing ophthalmologists, ophthalmology residents and fellows with the appropriate diagnostic testing and evidenced-based therapeutic options for managing patients afflicted with these conditions. Written and edited by leaders in the fields of ophthalmology, rheumatology, internal medicine, infectious disease, and oncology, each chapter addresses the latest advances in the field: from the advent of PCR technology, intraocular depot steroid implants, neoplastic and infectious diseases masquerading as uveitis, and the use of systemic immunomoduatory therapies (including biologic agents/humanized monoclonal antibodies).- Resué vydavatel
Keywords: uveitida; oftalmologie; uveitis; ophthalmology; elektronické knihy; sborníky; electronic books; papers of several authors